Evaluating wound-healing effect of silicon-zinc-boron-containing glycerohydrogel and its effect on mammary glands of high producing dairy cows - L. I. Drozdova; A. S. Barkova; M. N. Isakova; L. P. Larionov; V. V. Permikin; N. M. Starikov; T. G. Khonina (Ветеринария сегодня)
Cow’s milk quality, which may deteriorate due to inﬂammatory processes in the mammary glands, remains one of the important problems of dairy farming and requires eﬀective, safe and aﬀordable therapeutic agents. Nanocomposite silicon-zinc-boron-containing glycerohydrogel (Si-Zn-B-gel) may become a very good solution to the issue. The paper demonstrates wound-healing eﬀect of the glycerohydrogel and conﬁrms its eﬀectiveness for teat hyperkeratosis treatment indairy cows. Results of a rat burn model – based experiment suggest that Si-Zn-B-gel is a promising wound healing agent for topical use. Thus, on Day 9 complete re-epithelialization of the burn surface was observed, with ﬁbrous structures prevailing in the granulation tissue of the dermal layer, on Day 19 a mature scar was formed with a longitudinal alignment of collagen ﬁbers. The production tests conducted inhigh producing dairy cows have demonstrated good therapeutic eﬀect of the Si-Zn-B gel for teat-end hyperkeratosis and conﬁrmed its long-term eﬀect that helps to longer maintain the results achieved during treatment. After a 7-day treatment physiological structure of up to 27.8% teats improved, on Day 14 of the experiment no severe hyperkeratotic lesions were observed and the number of teats that correspond to the physiological norm was 72.2%. Analysis of the data collected shows that the Si-Zn-B-gel is eﬀective for teat-end hyperkeratosis treatment, thus, it prevents mastitis in animals and improves the milk quality.